Antioxidant activity and total phenolic content in Caulerpa filiformis (Chlorophyta) from Sechura Bay and Paracas Bay, Peru - Mamani, Joyce (2020)
In Peru, Caulerpa filiformis is a marine algae listed as an invasive species. For years, its distribution has been considered to be in the north coast (Isla Lobos de Afuera and Piura) until a recent report of its distribution in the central coast (Ancash, Lima, and Ica). The present investigation aims to determine the main groups of secondary metabolites, total phenol content, and antioxidant activity of the methanolic extract of C. filiformis from Sechura Bay (Piura) and Paracas Bay (Ica). The main chemical groups were determined through phytochemical screening, the content of phenols by the Folin–Ciocalteu method, and antioxidant activity by the ABTS method (2,2-azinobis-[3-ethylbenzothiazoline-6-sulfonic acid]) and 2,2′-diphenyl-1-picrylhydrazyl (DPPH). The phytochemical screening of the methanolic extract of C. filiformis from Sechura Bay and Paracas Bay revealed the presence of carbohydrates, polyphenols, tannins, flavonoids, lipids, alkaloids, steroids, and triterpenes for both extracts. The total phenol content of the extract of C. filiformis from Sechura Bay (39.31 ± 0.39 mg of AGE/g extract) was significantly higher (p < 0.05) than that from Paracas Bay (18.78 ± 0.31 mg of AGE/g extract). In the ABTS and DPPH assays, the antioxidant capacity of the Sechura C. filiformis extract (IC50 = 3.49 ± 0.01 and 2.18 ± 0.02 mg/mL) was significantly higher (p < 0.05) than that of the Paracas C. filiformis extract (IC50 = 6.41 ± 0.02 and 2.42 ± 0.04 mg /mL). These findings suggest that the methanolic extract of C. filiformis is a source of secondary metabolites with an antioxidant potential.